Does length of time since diagnosis in Parkinson’s disease influence heart rate variability? A cross-sectional study - Mileide Cristina Stoco-Oliveira; Heloisa Balotari Valente; Laís Manata Vanzella; Larissa Borba André; Mariana Viana Rodrigues; Franciele Marques Vanderlei; Augusto Cesinando de Carvalho; Luiz Carlos Marques Vanderlei (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Intrinsic changes in Parkinson's disease (PD) affect the autonomic nervous system, and the disease course can aggravate the initial condition. Although the impact of time since disease onset on autonomic modulation has already been studied in other populations, this has not yet been investigated in PD. Objective: To investigate the impact of the length of time since diagnosis on the cardiac autonomic modulation of individuals with PD and compare with healthy individuals. Methods: Fifty participants were divided into three groups: a control group (CG; n = 24) and two groups with PD, divided according to the median length of time since diagnosis (median = 5.5 years): below the median (PG1; n = 13) and above the median (PG2; n = 13). To evaluate cardiac autonomic modulation, heart rate was obtained beat-to-beat in the supine position over a 30-min period, and heart rate variability (HRV) indices were calculated using linear methods in the time and frequency domains. Results: There were no significant differences in HRV indices between the PG groups, or between the three groups regarding Mean RR, LFun, HFun and LF/HF ratio. Significant reductions in the RMSSD, SDNN, pNN50, LFms2 and HFms2 indices were observed in PG1 and PG2, compared with CG. Conclusions: The cardiac autonomic modulation of individuals with PD was not influenced by the time since diagnosis. However, reduced parasympathetic and global modulation were observed in these individuals, compared with controls. These results emphasize the importance of aerobic exercise for improving autonomic modulation among individuals with PD.